Nanopore Long-Read Guided Complete Genome Assembly of Hydrogenophaga intermedia, and Genomic Insights into 4-Aminobenzenesulfonate, p-Aminobenzoic Acid and Hydrogen Metabolism in the Genus Hydrogenophaga - Gan, Han M.; Lee, Yin P.; Austin, Christopher M. (Frontiers in Microbiology, 2017)
We improved upon the previously reported draft genome of Hydrogenophaga intermedia strain PBC, a 4-aminobenzenesulfonate-degrading bacterium, by supplementing the assembly with Nanopore long reads which enabled the reconstruction of the genome as a single contig. From the complete genome, major genes responsible for the catabolism of 4-aminobenzenesulfonate in strain PBC are clustered in two distinct genomic regions. Although the catabolic genes for 4-sulfocatechol, the deaminated product of 4-aminobenzenesulfonate, are only found in H. intermedia, the sad operon responsible for the first deamination step of 4-aminobenzenesulfonate is conserved in various Hydrogenophaga strains. The absence of pabB gene in the complete genome of H. intermedia PBC is consistent with its p-aminobenzoic acid (pABA) auxotrophy but surprisingly comparative genomics analysis of 14 Hydrogenophaga genomes indicate that pABA auxotrophy is not an uncommon feature among members of this genus. Of even more interest, several Hydrogenophaga strains do not possess the genomic potential for hydrogen oxidation, calling for a revision to the taxonomic description of Hydrogenophaga as “hydrogen eating bacteria”.